An Exploration of the Application of Regional Culture in International Chinese Language Education - Liu, Mingyuan (Journal of Educational Research and Policies, 2026)
In the context of globalization, international Chinese language education is no longer merely language teaching, but a comprehensive education that takes into account language proficiency development and cultural dissemination. Regional culture is an important part of Chinese culture, containing unique historical accumulation, folk customs and values, and is an important resource for enriching the content of international Chinese language teaching and improving the quality of teaching. Based on the close connection between regional culture and international Chinese language education, this article comprehensively analyzes the core value of the application of regional culture in international Chinese language education, explores specific ways to integrate regional culture into international Chinese language education, with the aim of providing theoretical references and practical lessons for improving the quality of international Chinese language education and promoting the multi-dimensional overseas dissemination of Chinese culture.